2020
DOI: 10.1021/acsami.0c19261
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Fatal Toxic Nerve Agents on Dry TiO2

Abstract: Despite a recent dramatically increased risk of using chemical warfare agents in chemical attacks and assassinations, fundamental interactions of toxic chemicals with other materials are poorly understood, and micromechanisms of their chemical degradation are yet to be established. This represents an outstanding challenge in both fundamental science and practical applications in combat against chemical weapons. One of the most versatile and multifunctional oxides, TiO 2 , has been suggested as a promising mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 67 publications
6
43
1
Order By: Relevance
“…In our study, we obtained free energy values of 62.75 to 5.24 kJ/mol within the 200–1000 °C temperature range. Recent experiments on CWAs have also been carried out under similar temperatures, including vapor-phase decomposition of DMMP (a sarin surrogate) at 500–800 K, sarin decomposition on TiO 2 nanoparticles at 1000 K, and decomposition of CWAs at 2000 K. ,, Collectively, all of these experiments showed that the temperature ranges studied in this work can also be achieved under operational conditions, and DIMP would decompose on the γ-Al 2 O 3 surface. Due to the structural similarity between DIMP and sarin, our calculations provide additional insight into decomposition mechanisms of both these molecules and elucidate atomic details of sarin decomposition on candidate metal oxide surfaces.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In our study, we obtained free energy values of 62.75 to 5.24 kJ/mol within the 200–1000 °C temperature range. Recent experiments on CWAs have also been carried out under similar temperatures, including vapor-phase decomposition of DMMP (a sarin surrogate) at 500–800 K, sarin decomposition on TiO 2 nanoparticles at 1000 K, and decomposition of CWAs at 2000 K. ,, Collectively, all of these experiments showed that the temperature ranges studied in this work can also be achieved under operational conditions, and DIMP would decompose on the γ-Al 2 O 3 surface. Due to the structural similarity between DIMP and sarin, our calculations provide additional insight into decomposition mechanisms of both these molecules and elucidate atomic details of sarin decomposition on candidate metal oxide surfaces.…”
Section: Discussionmentioning
confidence: 67%
“…Figure shows snapshots from our simulations depicting various DIMP adsorption configurations on the alumina surface. As suggested by prior theoretical calculations, the adsorption via the O atom of the P–OC 3 H 7 moiety is crucial for propene elimination. As the MD simulations progresses, we also observe interactions between the O (in the PO group) and Al atoms.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In our study, we obtained free energy values of 62.75 to 5.24 kJ/mol within the 200 -1000 • C temperature range. Recent experiments on CWAs have also been carried out under similar temperatures, including vapor phase decomposition of DMMP (a sarin surrogate) at 500 -800 K, 58 sarin decomposition on TiO 2 nanoparticles at 1000 K, 53 and decomposition of CWAs at 2000 K. 31,59,60 Collectively, all of these experiments showed that the temperature ranges studied in this work can also be achieved under operational conditions, and DIMP would decompose on the γ-Al 2 O 3 surface. Due to the structural similarity between DIMP and sarin, our calculations provide additional insight into decomposition mechanisms of both these molecules and elucidate atomic details of sarin decomposition on candidate metal-oxide surfaces.…”
Section: Discussionmentioning
confidence: 68%
“…As suggested by prior theoretical calculations, [51][52][53] the adsorption via the O atom of the P-OC 3 H 7 moiety is crucial for propene elimination. As the MD simulations progresses, we also observe interactions between the O (in the -P=O group) and Al atoms.…”
Section: Resultsmentioning
confidence: 86%